National or Global Uncertainty: Which Has a Greater Impact on Investment Demand? - Haifei Wang; Ekaterina Isupova (SAGE Open, 2025)
Investment demand depends on the level of uncertainty in the economy, it could have not only direct, but also indirect impact – it could significantly reduce the effectiveness of monetary policy by making investments less responsive to market signals. This issue has not been sufficiently studied in the economic literature; there are no empirical estimates of direct and indirect impacts of uncertainty on investment demand for a large sample of countries, so the scarcity of such studies has created a theoretical gap. Considering this research gap, our study used GMM estimator to analyze data for 161 countries from 2002 to 2022 to confirm that the interest elasticity of investment tends to be a function of the national level of uncertainty. This implies that reducing the interest rate may not be an effective way to stimulate investment under conditions of high uncertainty. In addition, the study empirically validated the impact of global uncertainty on investment in different countries. The findings contribute to investment theory by providing a better understanding of how uncertainty directly and indirectly influences investment demand. Several practical implications are proposed. However, the study has a limitation in that it only considers the dependence of investment elasticity on uncertainty as a single factor. There may be other significant factors that influence investment demand that were not included in the analysis. This fact creates a research gap that needs to be addressed in future studies.